USING OBLIQUE TECHNIQUE TO TEACHING TRANSLATION OF THE ELEVENTH GRADE STUDENDS OF SMA NURUL AMAL PALEMBANG - Ana Theriana (Esteem Journal of English Education Study Programme, 2018)
Abstract: In Indonesian educational system, English is one of the compulsory subjects instructed at school. The student learn English for the first time formally when they are still in the kindergarten up to the university as a foreign language, the students finds the difficulties to learn the four skills of English which are listening, speaking, reading and writing, and English also have some aspects in learning such as: structure, vocabulary, and also grammar.The problem of this study was â€œIs it effective to use oblique technique to the eleventh grade students of SMA NURUL AMAL Palembangâ€. The objective of this study was to find out whether or not it is effective to use Oblique Technique to the eleventh grade students SMA NURUL AMAL Palembang. The writer used pre-experimental method. The populations of this study were all the eleventh grade students of SMA NURUL AMAL Palembang in academic year 2011-2012. The sample of this study was 42 students, taken by using cluster random sampling method. The written tests were used to collect the data. The data were analyzed through matched t-test.